Tratamiento de la hemoptisis por embolización selectiva de las arterias brónquicas con tejido adiposo - Grillo, Angel (Cirugía del Uruguay, 1978)
In view of the encouraging results obtained in vascular occlusion by means of adipose tissue, the author performed 17 embolizations of bronchial arteries. Of this series, 17 cases were bilateral. amI in 9 patients hemoptysis was serious, whi'e in 3 others it was reJatively severe. The material employed for embolization was subcutaneous fatty tissue, which is maleable and easy to manage. Hemoptysis ceased in ali patients as soon as emboJization was achieved. One patient could not be emboJized due to the fact that he. presented an anatomical variation of bronchial arteries. 3 other patients presented severe anastomoses between intercostal and pulmonary circulation. Control was carried out with 8 patients, between the seventh and ninth months: -there was no rechanneling of occluded vessels -increase of collaterals was observed in one case -pathological anatomy was performed in one case Embolization of bronchial arteries is a pal'eative, occasionally definitive, treatment which can be applied to patients who are not in a condition to undergo any other type of therapy and/or whose general condition cannot improve otherwise. Bronchial arteriography is considered essential in determining lesiona! topography and indication to embolize.